Optimum Height of Plate Stiffener under Pressure Effect - Yousif, Mazin Victor; Naief, Nazar Kais M.; Hamad, Yahya M. (Nahrain University College of Engineering Journal, 2008)
The economical design of plate loaded by pressure can be obtained by using stiffeners instead of increasing the thickness of plate. The main subject of this work is to obtain the effect of stiffener height on the maximum stress in the plate subjected to pressure load. Different plate-stiffener sets are selected tofind the effects of stiffener thickness, plate dimensions and pressure, on the optimum stiffener height. The models under consideration are square plates clamped rigidly from four edges. Finite Element method is used to analyze 160 different models by using the Finite Element software package ANSYS version 11.Another analysis method based on maximum stress equation is used to analyze 30 models. The graphical comparison of results between two analytical methods is presented by a figure. It is found that the numerical results obtained by Finite Element Analysis converge to theoretical results. The optimum height of stiffener under above different effects is found. The critical pressure curves for square plate dimension sets are also presented.